Aluminium-mediated aromatic C-F bond activation: Regioswitchable construction of benzene-fused triphenylene frameworks - Suzuki, Naoto; Fujita, Takeshi; Amsharov, Konstantin; Ichikawa, Junji (Chemical Communications, 2016)
Selective synthesis of benzo[f]tetraphenes or benzo[g]chrysenes was achieved via aromatic C-F bond cleavage and unprecedented regioselective C-C bond formation depending upon the choice of aluminium reagents. On treatment with AlCl3, 2-(biphenyl-2-yl)-1-fluoronaphthalenes afforded exclusively benzo[f]tetraphenes via C-C bond formation on the carbon atom γ to the original position of the fluorine substituent. In contrast, α-selective C-C bond formation was promoted by treatment with γ-Al2O3 to give benzo[g]chrysenes.
CRIS-Team Scopus Importer:2023-03-20